Peningkatan Hasil Belajar Fisika Melalui Model Problem Based Learning (PBL) - Suripta suripta (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
This research is aiming to improve student’s achievements in learning physics. This research uses classroom action research with data analysis using qualitative descriptive. This research was conducted at SMAN 106 Jakarta with two cycles. Test results and documentation used to collect data SMAN 106 is chosen as a place of research with two-cycle. From the research we get an average score 72 on the pre-cycle assessment, there an increasing score on the first and second phases became 80,00 and 92,00. From the 1st and 2 st fase, it shows that the result of the model the learning has been improved after conduct a model learning with problem-based learning. So, we can conclude that problem-based learning can improve student achievements in physics.